2020
DOI: 10.1109/access.2020.2995567
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomegaly Detection on Chest Radiographs: Segmentation Versus Classification

Abstract: In this study, we investigate the detection of cardiomegaly on frontal chest radiographs through two alternative deep-learning approaches -via anatomical segmentation and via image-level classification. We used the publicly available ChestX-ray14 dataset, and obtained heart and lung segmentation annotations for 778 chest radiographs for the development of the segmentation-based approach. The classification-based method was trained with 65k standard chest radiographs with image-level labels. For both approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 59 publications
0
32
0
1
Order By: Relevance
“…This indicates that most of these categorical disagreements are simply due to CTR estimation noise around the 0.5 threshold (borderline cases) rather than significant departures in estimation between model and manual method. These near-boundary error cases were forgivable and mentioned in another study [9].…”
Section: ) Error Analysismentioning
confidence: 66%
See 2 more Smart Citations
“…This indicates that most of these categorical disagreements are simply due to CTR estimation noise around the 0.5 threshold (borderline cases) rather than significant departures in estimation between model and manual method. These near-boundary error cases were forgivable and mentioned in another study [9].…”
Section: ) Error Analysismentioning
confidence: 66%
“…Similarly, two human readers have an MAE of 0.0123, or a mean difference of -0.0076 ± 0.0136, with 95% limits of agreement from -0.0192 to 0.0343. Two other studies [7], [9] have benchmarked the performance of algorithms against trained CXR readers with comparable performances to our own. However, our study is, to the best of our knowledge, the only study where testing was performed on an external validation dataset (i.e.…”
Section: B Model Performance Benchmarked Against Manual Methods 1) Comparison Of Ctr Mean Errormentioning
confidence: 77%
See 1 more Smart Citation
“…Studies have previously shown that machine learning algorithms, namely, SVM, RF (random forest), LR (logistic regression), BPNN (back propagation neural network), and MLP (multilayer perceptron) are utilized successfully for decision-making tools to predict heart disease based on individual information. Various studies revealed the hybrid model merits that achieved good performance in heart disease prediction, namely, RF with a linear model, MLP, Bayes Net (BN), majority voting of NB, and RF and two stacked SVMs, respectively [14]. Kalia Orphanou et al, in the NB classification model, the TARs (Temporal Association Rules) feature is used for diagnosing heart disease.…”
Section: Part 2 Is 'Diastole'mentioning
confidence: 99%
“…This has been accelerated by the availability of large, publicly available clinical imaging datasets [24,12]. Deep learning methods focus on using convolutional neural networks to either assign a binary cardiomegaly diagnosis based on the input image [19], or to use U-Net networks to segment the heart and lungs from the image and estimate the CTR [18,23].…”
Section: Introductionmentioning
confidence: 99%